2013
DOI: 10.3389/fncel.2012.00060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of retinal ganglion cell degeneration in glaucoma and future prospects for cell body and axonal protection

Abstract: Glaucoma, which affects more than 70 million people worldwide, is a heterogeneous group of disorders with a resultant common denominator; optic neuropathy, eventually leading to irreversible blindness. The clinical manifestations of primary open-angle glaucoma (POAG), the most common subtype of glaucoma, include excavation of the optic disc and progressive loss of visual field. Axonal degeneration of retinal ganglion cells (RGCs) and apoptotic death of their cell bodies are observed in glaucoma, in which the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 165 publications
(186 reference statements)
3
72
0
Order By: Relevance
“…OCT was performed as an indicator of progressive neural retinal pathology in animal models of retinal degeneration [38, 39]. In the present study, we found a significant reduction in overall retinal thickness as well as all four quadrants, depending on the OCT scanning, in db/db mice when compared with control mice at the age of 28 weeks.…”
Section: Discussionsupporting
confidence: 66%
“…OCT was performed as an indicator of progressive neural retinal pathology in animal models of retinal degeneration [38, 39]. In the present study, we found a significant reduction in overall retinal thickness as well as all four quadrants, depending on the OCT scanning, in db/db mice when compared with control mice at the age of 28 weeks.…”
Section: Discussionsupporting
confidence: 66%
“…In retinal disease such as retinopathy of prematurity, diabetic retinopathy, age-related macular degeneration and glaucoma, an insufficient supply of oxygen or nutrients, may occur during conditions of disturbed hemodynamics or vascular defects, results in highly impaired cellular oxygen balance, and retinal neurons become hypoxic (Kaur et al, 2009, 2012; Munemasa and Kitaoka, 2012). Among the retinal neurons, retinal ganglion cells (RGCs) are the predominant components that undergo hypoxic injury (Abu-El-Asrar et al, 2004; Caprara and Grimm, 2012; Munemasa and Kitaoka, 2012), for they are the ultimate neurons in retina that consume large quantities of energy to convey visual information to the brain (Sanes and Masland, 2015). Hypoxia-related disorders enhance or induce the death of RGCs in the retina, resulting in irreversible vision loss, most of which through apoptosis (Kaur et al, 2009; Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In glaucoma, RGCs might die not only because of axonal degradation but also because of the activation of glial cells and the oxidative stress of immunological processes (Munemasa and Kitaoka 2012). The relative importance of these mechanisms is unknown.…”
Section: The Retinal Ganglion Cellmentioning
confidence: 99%